تقييم سريري للصفائح التقويمية الموضوعة في المنطقة الخلفية من الفك السفلي والمثبتة ببراغي طول 6 ملم - قصبة سامر (Latakia University Journal -Medical Sciences Series, 2019)
This study aims at assessing the clinical success of Y-shape miniplate as orthodontic anchorage, the safety of using 6-mm self-drilling fixation miniscrews (FMSs), and patients’ postoperative complications. A total of 26 consecutive patients and 52 Y-shaped miniplates in the both sides of the mandibule were enrolled. The miniplates were fixed in place with 116 self-drilling FMSs. During healing period, the heath of adjacent teeth and inferior alveolar nerve were evaluated, and any related complication was recorded. There was no evidence to suggest inferior alveolar nerve or adjacent tooth disturbance during or after placement of the miniplates. No miniplate failed before the end of treatment (0% failure rate). Only one case with acute infection was successfully treated and the miniplate was not removed and remained stable during orthodontic loading. No chronic inflammation with tissue proliferation around the miniplate in any miniplate. Mandibular orthodontic miniplate fixated with 6-mm FMSs in the area between the first and second molars has a high success rate with few side effects or complications affect adjacent roots or the inferior alveolar nerve. هدفت هذه الدراسة إلى تقييم نجاح استخدام الصفائح التقويمية ذات الشكل حرف Y كدعائم تقويمية، ومدى أمان استعمال براغي التثبيت ذاتية الإدخال بطول 6 ملم في المنطقة بين الرحتين السفليتين الأولى والثانية، والاختلاطات الناتجة عن استعمالها. تمت الدراسة على 26 مريض خضعوا لعمليات تثبيت52 صفيحة تقويمية في طرفي الفك السفلي. تم تثبيت الصفائح باستخدام 116 برغي تثبيت. خلال فترة الشفاء تم تحري سلامة كلاً من الأسنان المجاورة والعصب السني السفلي، وتسجيل أي اختلاط ناتج عن المعالجة. لم يوجد أي دليل على تأذي أي من الأسنان أو العصب السني السفلي خلال وبعد وضع الصفائح. لم تفشل أي صفيحة قبل نهاية مدة المعالجة (نسبة فشل 0 %). حدثت فقط حالة واحدة لالتهاب حاد تم معالجته بنجاح ولم يتم إزالة الصفيحة لأنها بقيت ثابتة خلال فترة التحميل التقويمي. لم يتم تسجيل أي حالة التهاب نسج رخوة مزمن تكاثري حول الصفائح. يترافق وضع الصفائح التقويمية المثبتة ببراغي طول 6 ملم بين الرحتين الأولى والثانية السفلية بنسبة نجاح عالية مع عدد قليل جداً من الاختلاطات خاصة فيما يتعلق بالأسنان المجاورة أو العصب السني السفلي.